Learning Media Innovation by Islamic Religious Education Teachers in Indonesian Elementary Schools: A Qualitative SWOT Analysis - Hildayasnah, Mauludfi; Arifin, Moch. Bahak Udin By; Daud, Normadiah Binti (Journal of Islamic Education Research, 2026)
This study investigates learning media innovation implemented by Islamic Religious Education teachers in Indonesian elementary schools and examines how these innovations align with the school’s vision and mission while enhancing instructional quality. The purpose of this study is to identify the forms of learning media innovation, evaluate their pedagogical implications, and analyze internal and external factors affecting their sustainability using a SWOT-based strategic framework. A qualitative case study was conducted at SD Muhammadiyah 1 Candi Sidoarjo, involving one principal, two Islamic Religious Education teachers, and purposively selected Grade III and Grade V students. Data were collected through semi-structured interviews, classroom observations, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, integrated with SWOT analysis, to ensure systematic interpretation and triangulation. The findings reveal four dominant categories of learning media: digital presentations, audio-visual videos, concrete teaching aids, and teacher-developed contextual modules. These innovations significantly increased students’ engagement, participation, classroom interaction, and conceptual understanding of religious content. Institutional strengths include leadership support, collaborative teacher culture, and adequate infrastructure, while weaknesses involve limited digital devices, varying levels of technological competence, and time constraints for media preparation. Opportunities arise from technological advancement and institutional partnerships, whereas threats relate to technical complexity and financial limitations. The novelty of this study lies in conceptualizing learning media innovation as a strategic and institutional ecosystem rather than merely a technical classroom practice. This study contributes theoretically by extending differentiated learning theory to Islamic Religious Education across cognitive, affective, and spiritual domains, and practically by offering a strategic framework to guide sustainable media innovation in primary religious education contexts.